Procedural efficacy and safety of standardized, ablation index guided fixed 50 W high‐power short‐duration pulmonary vein isolation and substrate modification using the CLOSE protocol. (19th July 2021) - Francke, Alexander; Taha, Nadja S.; Scharfe, Frank; Schoen, Steffen; Wunderlich, Carsten; Christoph, Marian
Abstract: Introduction: Ablation index (AI)‐guided ablation according to the CLOSE protocol is very effective in terms of chronic pulmonary vein isolation (PVI). However, the optimal radiofrequency (RF) power remains controversial. Here, we thought to investigate the efficiency and safety of an AI‐guided fixed circumferential 50 W high‐power short‐duration (HPSD) PVI using the CLOSE protocol. Methods and Results: In a single‐center trial, 40 patients underwent randomized PVI using AI‐guided ablation without esophageal temperature monitoring. In 20 patients a CLOSE protocol guided fixed 50 W HPSD was followed irrespective of the anatomical localization. Twenty subjects were treated according to the CLOSE protocol with standard power settings (20 W posterior and 40 W roof and anterior wall). In addition, 80 consecutive patients were treated according to the HPSD protocol to gather additional safety data. All patients underwent postprocedural esophagogastroduodenoscopy to reveal esophageal lesions (EDELs). The mean total procedural time was 80.3 ± 22.5 in HPSD compared to control 109.1 ± 27.4 min ( p  < .001). The total RF‐time was significantly lower in HPSD with 1379 ± 505 s versus control 2374 ± 619 s ( p  < .001). There were no differences in periprocedural complications. EDEL occurred in 13% in the HPSD and 10% in the control group. EDEL occurring in the 50 W HSDP patients were smaller, more superficial, and had a faster healing tendency. Conclusion: A fixed 50 W HPSD circumferential PVI relying on the AI and CLOSE protocol reduce the total procedure time and the total RF time, without increasing the complication rates. The incidence of EDELs was similar using 50 W at the posterior atrial wall.